Regenerasi perkotaan, alienasi, dan abolisi kelas pekerja dalam budaya politik Inggris pasca industri - Linggar R D Putra (Masyarakat, Kebudayaan dan Politik, 2015)
This paper looks at the phenomena of urban regeneration that has been happening after de-industrialization within the British political-historical context. Since the 1970s economic turbulence, under the Thatcher Conservative Regime, Britain experiences political-economic transformation that hegemonically restores its society through the implementation of market economic principles and the public policy control to reduce state roles in the welfare distribution process. One of the strategies is by re-ordering industrial cities through the urban regeneratiopool, Britain, this paper aims to trace socio-political aspects driving the urban regeneration andn project considered as the deprived ones whilst still have economic potentials for the future capital accumulation. Drawing on an ethnographic research carried out in the summer 2014 in Liver its cultural implication to whom particularly categorised as the urban working class. Anthropological analysis is carried out by conforming dialectically information on the field and theories regarding on the informant and researcher cultural background to avoid bias result. The result shows that urban regeneration is the continuity of class struggle which embedded in the British cultural and political history. Furthermore, cultural-political factors which are inherited by the Thatcher Conservative regime in urban regeneration policies are very dominant affecting on the weakening of the urban working class existence in the British post industrial era.